The Practical Imperialist : Letters from a Danish Planter in German East Africa 1888-1906 - Parpart, Jane,; Rostgaard, Marianne, (Brill Book Archive Part 1, ISBN: 9789004472495., 2006)
This book provides a rare opportunity to follow the daily life on and around plantations and towns in the first years of the German colonial presence in East Africa, as seen through the eyes of a Danish master farmer working for the German East Africa Company. There are few memoirs and personal letters from these years, and existent letters are primarily by explorers, colonial officials, missionaries or the occasional settler. Lautherborn's material provides one of the very few entry points into the daily business of colonial expansion and consolidation in the early years of German East Africa as seen through the eyes of a practical man trying to do a job in a complex and changing world.